High detection rate in [18F]PSMA-1007 PET: interim results focusing on biochemical recurrence in prostate cancer patients - Watabe, Tadashi; Uemura, Motohide; Soeda, Fumihiko; Naka, Sadahiro; Ujike, Takeshi; Hatano, Koji; Sasaki, Hidetaka; Kamiya, Takashi; Shimosegawa, Eku; Kato, Hiroki; Cardinale, Jens; Tateishi, Ukihide; et al. (Annals of nuclear medicine, 2021)
18F-labeled prostate-specific membrane antigen (PSMA) ligand, [18F]PSMA-1007, has the benefit of a higher synthetic yield and minimal excretion in the urine. High detection efficacy was reported in biochemical recurrence (BCR) of prostate cancer after radical prostatectomy. Thus, we evaluated the preliminary diagnostic utility of [18F]PSMA-1007 PET in patients with prostate cancer, focusing on the BCR which is not detected on conventional imaging.
Gesehen am 27.01.2022
Im Titel ist "18" hochgestellt